2000
DOI: 10.1007/s001470050701
|View full text |Cite
|
Sign up to set email alerts
|

Comparative report on transplantation and relevant ethical problems in five European countries, and some reflections on Japan

Abstract: Comparison of transplantation medicine in Sweden, Denmark, Germany, Spain and Portugal reveals many and important differences with respect to frequency of transplantations, frequency of life donations, legal regulations and influence of the family on organ donation. The differences observed are at least partly related to cultural and value differences between the various countries, but many questions need to be studied systematically and in more detail before useful conclusions can be drawn. One study would ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, deceased organ donation rates in these countries vary considerably (6). These variations have been attributed, among other factors, to mainly cultural differences (7). Thus, in the year 2000, Fleischhauer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, deceased organ donation rates in these countries vary considerably (6). These variations have been attributed, among other factors, to mainly cultural differences (7). Thus, in the year 2000, Fleischhauer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the year 2000, Fleischhauer et al. (7) presented a study about donation and transplantation carried out in five European countries (Sweden, Denmark, Germany, Spain and Portugal), indicating that the differences observed were partly related to cultural differences. If this is really the case, in Spain we are in danger of experiencing a decrease in our donation rates due to the arrival of a considerable number of citizens from other countries (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been seen that donation rates in these countries are very disparate (12). These differences have been attributed, among other factors, mainly to cultural differences (9). However, although populational studies about attitude toward organ donation (10–11) provide disparate acceptance rates according to the country, there are generally favorable attitudes in different European countries, with rates ranging from between 65% and 90%.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation results detect a sizeable but lower impact of potential donor pool on deceased donation rates than previously predicted. 9 Column (3) shows that presumed consent countries exhibit 5.3 percent higher deceased donation rates on average compared to informed consent countries after accounting for total per capita health expenditure, death rates caused by cerebro vascular diseases, motor vehicle accidents and homicides, civil rights and liberties and legal systems, whose coefficients are statistically significantly different from zero at conventional levels. 10 The impact of presumed consent laws on deceased donation can be challenged by the fact that significant variations in deceased donation rates are accounted by the way consent laws are practiced and not only by the legal framework.…”
Section: Resultsmentioning
confidence: 97%
“…The reason is that without country-specific effects, the consent legislation variable soaks up most of the explanatory power of the unobserved heterogeneity and shows a higher-than-otherwise impact of presumed consent laws. 9 The control of supply measures for donation policy purposes creates a paradox in organ collection because the promotion of deceased donation through continuous education and awareness programs contradicts policies that aim to reduce the prevalence of motor vehicle accidents and hand-gun crimes by raising awareness [2]. Recently, Dickert-Conlin et al [7] found that organ donations due to motor vehicle accidents increase by 10 percent following helmet law repeals and that a nationwide elimination of helmet laws in the US would increase the annual supply of organ donors by less than 1 percent.…”
Section: Resultsmentioning
confidence: 97%